Rome's holy mountain: the Capitoline Hill in late antiquity - Moralee, Jason (Oxford studies in late Antiquity, 2020)
"Rome's Holy Mountain is the first book to chart the history of the Capitoline Hill in Late Antiquity, from the third to the seventh centuries CE. It investigates both the lived-in and dreamed-of realities of the hill in an era of fundamental political, religious, and social change" --